IMPLEMENTATION OF FISHER-YATES SHUFFLE ALGORITHM IN ANDROID-BASED JAVANESE BATIK CULTURE EDUCATION GAME - Ben Rahman; Mochamad Naufal Shofy; Septi Andryana (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
Batik, as one of Indonesia's precious cultural heritages, has a variety of motifs in the art of batik in this country. The preservation of batik is important and the success of educational games in supporting this goal has been proven. Understanding the complex meaning and philosophy of batik is difficult given the variety of motifs. Therefore, this research creates an Android game that incorporates elements of batik culture to introduce the meaning and philosophy of Indonesian batik to the next generation. Android technology makes learning more flexible, allowing unrestricted access to information. By following the Game Development Life Cycle (GDLC) method and integrating the Fisher-Yates Shuffle algorithm and Finite State Machine (FSM), this game takes players on an adventure against Non-Playable Character (NPC) characters using the FSM model. The Fisher-Yates Shuffle algorithm is used to randomize 10 questions, making each game session unique. The algorithm test results showed an average question execution time of about 35.6 microseconds, indicating stable performance despite variations in each trial. The alpha test results showed an average score of 87%, covering aspects of information readability, responsiveness, player motivation, combat experience, educational benefits, as well as satisfaction, and game design that showed good performance. Thus, this research succeeded in creating an educational game that is entertaining and educational, as well as helping to maintain and introduce batik cultural heritage to the next generation.